PENGUATAN INSTITUSI KELOMPOK TANI HUTAN KEMASYARAKATAN: PENGABDIAN KEPADA MASYARAKAT DI GUNUNG KIDUL YOGYAKARTA - Ramdani, Rijal; Radhica, Dicky Dwi; Koma, Desi Riza Ayu (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Forest Policy provides an opportunity for the Sedyo Makmur Forest Farmers Group in Gunungkidul District, Yogyakarta, to manage 115 hectares of state-owned forest for 30 years. However, based on observations and interviews, we found that (1) the Sedyo Makmur Forest Farmer Group did not yet have adequate managerial and administrative systems; (2) it was not able to meet the administrative requirements to apply for a permit (Timber Forest Product Utilization Business License (IUPHHK HKm)); (3) it did not yet understand the sustainable logging system; and (4) it has limited capacity to sell forest products. Through this community service program, we assisted the Sedyo Makmur group by providing: (1) education to the management and members of the forest farmer group on administrative preparation, organizational governance, and building organizational networks; (2) training on the administrative system for applying for HKm IUPHHK permits in accordance with regulations; (3) preparation of the Felling Plan and Annual Work Plan; (4) data collection and calculation of timber potential; (5) counseling on sustainable forest timber harvesting systems in accordance with the principles of sustainable forestry; and (6) training on timber product marketing systems through networking with the timber industry. We expected to strengthen Sedyo Makmur’s institutional capacity so that it can become a productive institution capable of managing forests sustainably and obtaining logging rights through an appropriate marketing system. The results of this community service activity show that members of the Sedyo Makmur group have gained a better understanding of the materials delivered during the program. This understanding has been implemented through improvements in administrative management, organizational governance, and timber logging practices in accordance with established procedures. However, the group still faces challenges in marketing timber products, particularly in utilizing digital technology and online platforms for broader market access.Kebijakan Hutan Kemasyarakatan memberikan kesempatan kepada Kelompok Tani Hutan (KTH) Sedyo Makmur di Kabupaten Gunungkidul, D.I. Yogyakarta, untuk mengelola hutan milik negara seluas 115 hektar selama 30 tahun. Namun, berdasarkan pengamatan dan wawancara, (1) KTH belum memiliki sistem manajerial dan administrasi yang memadai; (2) belum mampu memenuhi persyaratan administrasi untuk mengajukan izin (Izin Usaha Pemanfaatan Hasil Hutan Kayu (IUPHHK) HKm); (3) belum memahami sistem penebangan lestari; dan (4) belum memiliki kemampuan untuk memasarkan hasil hutan. Melalui program pendampingan ini, Tim Pengabdian kepada Masyarakat mendampingi Sedyo Makmur dengan memberikan 1) edukasi kepada pengurus dan anggota kelompok tani hutan dalam penyiapan administrasi, tata kelola organisasi, dan membangun jejaring organisasi; 2) pelatihan sistem administrasi pengajuan izin IUPHHK HKm yang sesuai dengan peraturan; 3) penyusunan Rencana Tebang dan Rencana Kerja Tahunan; 4) pendataan dan penghitungan potensi kayu; 5) penyuluhan sistem pemanenan kayu hutan lestari sesuai dengan prinsip-prinsip kehutanan lestari; dan 6) pelatihan sistem pemasaran produk kayu melalui jejaring dengan industri perkayuan. Tim Pengabdian Masyarakat diharapkan dapat memperkuat kelembagaan Sedyo Makmur sehingga Sedyo Makmur dapat menjadi lembaga yang mandiri, mampu mengelola hutan secara lestari, dan memperoleh hak penebangan melalui sistem pemasaran yang tepat. Hasil dari pengabdian ini adalah KTH Sedyo Makmur bisa memahami materi yang kemudian diimplementasikan dalam bentuk pembuatan administrasi, tata kelola organisasi dan penebangan kayu sesuai prosedur. Namun, dalam hal pemasaran kayu dengan cara memanfaatkan teknologi, mereka masih mengalami kesulitan.